2011
DOI: 10.1088/0004-637x/737/1/12
|View full text |Cite
|
Sign up to set email alerts
|

THE CO-TO-H2CONVERSION FACTOR FROM INFRARED DUST EMISSION ACROSS THE LOCAL GROUP

Abstract: We estimate the conversion factor relating CO emission to H 2 mass, α CO , in five Local Group galaxies that span approximately an order of magnitude in metallicity -M 31, M 33, the Large Magellanic Cloud (LMC), NGC 6822, and the Small Magellanic Cloud (SMC). We model the dust mass along the line of sight from infrared (IR) emission and then solve for the α CO that best allows a single gas-to-dust ratio (δ GDR ) to describe each system. This approach remains sensitive to COdark envelopes H 2 surrounding molecu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

114
864
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 584 publications
(981 citation statements)
references
References 79 publications
114
864
2
1
Order By: Relevance
“…Within the Milky Way and Local Group (aside from the Small Magallenic Cloud [SMC]), the conversion factor appears to display a remarkably narrow range of X CO ≈ 2 − 4 × 10 20 cm −2 /K km s −1 (or α CO ≈ 3 − 6 M pc −2 (K km s −1 ) −1 Bloemen et al, 1986;Solomon et al, 1987;Blitz et al, 2007;Delahaye et al, 2011;Leroy et al, 2011;Donovan Meyer et al, 2012b,a). The independent H 2 mass measurements in these observations come from virial mass measurements, dust to gas ratio assumptions (or measurements), and γ-ray observations.…”
Section: Deriving H 2 Gas Masses From High-redshift Galaxiesmentioning
confidence: 99%
“…Within the Milky Way and Local Group (aside from the Small Magallenic Cloud [SMC]), the conversion factor appears to display a remarkably narrow range of X CO ≈ 2 − 4 × 10 20 cm −2 /K km s −1 (or α CO ≈ 3 − 6 M pc −2 (K km s −1 ) −1 Bloemen et al, 1986;Solomon et al, 1987;Blitz et al, 2007;Delahaye et al, 2011;Leroy et al, 2011;Donovan Meyer et al, 2012b,a). The independent H 2 mass measurements in these observations come from virial mass measurements, dust to gas ratio assumptions (or measurements), and γ-ray observations.…”
Section: Deriving H 2 Gas Masses From High-redshift Galaxiesmentioning
confidence: 99%
“…Recent studies have also shown that a CO in low-metallicity galaxies can be substantially higher than the Galactic value (e.g., Leroy et al 2011;Schruba et al 2012;Bolatto et al 2013) and hence we restricted our sample to galaxies with an oxygen abundance value of [ ]  + 12 log O H 8.4, using the average of their characteristic metallicities derived from a theoretical calibration and an empirical calibration as recommended by Moustakas et al (2010).…”
Section: Model-extrapolated Lower Temperature T ℓmentioning
confidence: 99%
“…Since H 2 can self-shield from UV photons in regions where CO is photodissociated (Wolfire et al 2010), at low metallicity, not only is the CO abundance reduced, but as dust opacity is reduced and ionized regions become hotter and more porous, a CO,Gal can severely underestimate the molecular gas mass. Considerable effort has been invested in detecting and interpreting CO emission at metallicity 50 times lower than the solar metallicity, [ ] + 12 log O H ∼7.0, to assess the molecular gas content (Leroy et al 2011;Schruba et al 2012;Cormier et al 2014;Rémy-Ruyer et al 2014). Dust emission can be used to estimate the molecular gas mass in the ISM, assuming a constant DGR; however, it is essential to know the change in DGR with metallicity.…”
Section: Effect Of Dust Temperature On the Warm H 2 Fractionmentioning
confidence: 99%
“…As is usually done for nearby galaxies 7,15 the GDR in the star-forming clumps is taken as the ratio of atomic gas to dust in the diffuse region of the disk. This works because (1) the atomic gas dominates the total gas mass in the diffuse regions, and (2) the GDR is roughly constant in star-forming disks after removing the metallicity gradients 15,21 .…”
mentioning
confidence: 99%